Body mass index and persistent hypertension in patients with hypertension disorders of pregnancy one-year postpartum - Anguzu, Ronald; Livergood, M Christine; Fitzgerald, Garrett; Palatnik, Anna (American Journal of Obstetrics & Gynecology, 2023)
This was a retrospective cohort study of patients with HDP (defined as gestational hypertension or preeclampsia) in a single US Midwestern academic institution from 2014 to 2018. The primary outcome was persistent hypertension at one-year postpartum, defined as systolic blood pressure (BP) ≥130 mm Hg or diastolic BP ≥80 mm Hg. Both categorical BMI (model 1) (normal, overweight, and obese) and continuous BMI (model 2) were examined as predictor variables. Descriptive statistics and logistic and linear regression analyses were run for categorical and continuous BMI respectively. Odds ratios (OR) and 95% confidence intervals (CI) were reported.
Keywords: Postpartum; Pregnancy; Hypertension disorders; Body mass index